Pengaruh Modal Kerja, Literasi Keuangan, Terhadap Kinerja UMKM Di Kota Medan - Lubis, Putri Amalia (Ali Institute of Research and Publication, 2025)
This study aims to explore the impact of the implementation of working capital, and financial literacy on the performance of MSMEs in Medan City. The method applied in this study is quantitative, with data obtained through questionnaires and measured using a Likert scale. The sample discussed in this study is all medium-sized MSMEs in Medan City, a purposive sampling technique was used to select samples based on certain criteria, with calculations using the Slovin method, resulting in 99 respondents from MSMEs in the service, culinary, and goods sectors. Data analysis was carried out using multiple linear regression with the help of the SPSS 23 application. The findings of this study indicate that the implementation of the working capital has a significant effect on MSME performance, while financial literacy has a positive and significant impact on MSME performance. Finally, simultaneous analysis shows that the implementation of the working capital, and financial literacy together have a positive and significant effect on MSME performance.